The Seasonal Variations of the Thermocline in the Banda Sea and its Water Mass Characteristics - Simon Tubalawony; Ronald D. Hukubun; Degen E. Kalay (Jurnal Penelitian Pendidikan IPA, 2024)
This research was conducted to examine the seasonal variations in the Banda Sea's thermocline layer and its water mass characteristics. The research was conducted by analyzing Argo Float data. The data consists of six observation stations in West Season and Transitional Season II, and four stations in Transition Season I and East Season The thermocline layer thickness was identified based on the depth where the temperature decreased ≥ 0.05oC/m. The thermocline layer's distribution of depth and thickness and the distribution of temperature and salinity seasonally in the thermocline layer were analyzed with Microsoft Excel 2010. The analysis results showed that East Season and Transition Season II have a shallower upper boundary depth of the thermocline layer, a deeper lower boundary of the thermocline layer, and the thermocline layer is thicker when compared to the West Season and Transition Season I. The average temperature distribution is higher and the average salinity is lower in the West Season and Transition Season I. The mean rate of change in salinity and temperature in the thermocline layer seasonally ranged from 0.002-0.004 PSU/m and 0.06-0.08oC/m. The thermocline layer's stratification is stronger in the West Season and Transition Season I.